Amoxicillin Morbilliform Drug Eruption in Pediatric Male with Poor Feeding Treated with Cyproheptadine: A Case Report - Daniel Nguyen; Christina Vo (University Library System, University of Pittsburgh, 2018)
Background: Cyproheptadine (CY) is an antihistaminic agent that is commonly used for symptom relief in skin conditions. The most common pattern of cutaneous drug eruption in children is the exanthematous type, with the penicillin family often cited. CY is also an antiserotoninergic agent with the side effect of appetite stimulation and has been used in children with poor feeding and poor weight gain. The Case: We report a case of a 31-month-old male patient seen in the outpatient setting with a diffuse morbilliform rash after use of amoxicillin for right otitis media. The patient was a post-operative congenital heart disease (CHD) patient, actively being treated with CY for feeding difficulties and low weight often seen in the CHD population. Amoxicillin was discontinued, while CY was continued. The patient did not encounter any pruritic symptoms during morbilliform rash, while weight gain of 3.1 kg occurred over a 9 months period, increasing patient from the 10th to 41st percentile. Conclusion: A review of studies on CY has shown antiallergic properties in histamine-mediated hypersensitivity reactions, most likely through H1 receptor antagonism.  This mechanism may be used to address the pruritic symptoms during type IV T-cell mediated hypersensitivity cutaneous drug eruptions. CY also possesses 5-HT receptor antagonist properties with demonstrated ability to increase appetite in poor feeding pediatric patients. CY was successfully used for this purpose in our CHD patient.